Strangers in the Land: Traveling Texts, Imagined Others, and Captured Souls in Jewish, Christian, and Muslim Traditions in Late Antique and Mediaeval Times - Hjälm, Miriam L.; Zawanowska, Marzena (Religious Studies, Theology and Philosophy E-Books Online, Collection 2024., 2024)
This volume explores the ways in which representatives of different monotheistic traditions perceived and described or experienced themselves as "the other." This central category - which includes not only those of different religions, but also converts, foreigners, sectarians, and women - is studied from various perspectives in a range of texts composed by Jewish, Christian, and Muslim authors during late antique and mediaeval times. Conceptualizations of such "others" are often intrinsically related to the idea of exile, another important category that is analysed in this work.